Acceso a la Justicia a través de la Judicatura. - Guevara, Santiago D. (2021)
In the project called Access to justice through the Council of the Judiciary for the community, activities have been carried out through which students attend the Council of the Judiciary to carry out their hours of relationship with society and pre-professional practices, it has been defined the number of 80 semester hours for its fulfillment, each student who is registered in the project has an office number that has been admitted to the Imbabura Judicial Council. Students own their follow-up folder for its evaluation, control and monitoring by the assigned tutor teacher who visits them periodically.